Control interno de los procesos contables de la Empresa Comercial Oruliaceros de la ciudad de Babahoyo en los periodos 2020-2021. - Pazmiño Santillán, Washington Steven (2022)
The present study focuses on proposing an efficient Internal Control system that allows the Commercial Oruliaceros company in the periods 2020-2021, to achieve more dynamic processes that generate optimal and profitable results, where the causes that exist in the entity can be identified, the purpose of developing this work was to obtain information to help write accounting process guides that meet the needs of the organization and allow it to optimize commercial activities. The risk factors identified as an inadequate control in the company where they affect the activities in the financial area, the focus of this work allows to review and identify solutions to eliminate deficiencies in liquidity, identify tools to examine the financial statements. A type of documentary research was used to find selective and aggregate information, documents, library bibliographies that help develop the research topics. Instead, the descriptive because it is useful to describe, record, analyze and interpret a business; and understanding the internal control of accounting processes. The present research work used a qualitative methodology for the interview with the purpose of data collection in compiling information directly with a reliable source to obtain good better results in the profitability of the company.